Microbial innovations in phosphorus removal: Advancing biological phosphorus removal for sustainable environmental management and resource recovery - Verma, Geeta; Mitra, Debasis; Rani, Anju; Chaudhary, Priya (Edelweiss Applied Science and Technology, 2025)
Understanding the microbial basis of phosphorus (P) removal is essential for enhancing biological treatment systems. Among various approaches, the Enhanced Biological Phosphorus Removal (EBPR) process utilizes polyphosphate-accumulating organisms (PAOs) that take up and store phosphorus as intracellular polyphosphate under aerobic conditions and release it anaerobically, facilitating practical phosphorus cycling. This cyclical mechanism plays a central role in phosphorus removal and is driven by the distinct metabolism of these microbes. However, the presence of glycogen-accumulating organisms (GAOs) can reduce phosphorus removal efficiency. Extensive research over the past few decades has improved our understanding of how microbial interactions, metabolic pathways, and environmental controls influence system performance. This review traces the progression of PAO-centered strategies, explores the biochemical and ecological mechanisms involved, and highlights recent advances in molecular techniques used for the oversight and optimization of EBPR processes. It also identifies persistent gaps in our understanding of PAO physiology and considers how improved recovery methods could support more sustainable, resource-efficient wastewater treatment.